Label-free biosensing of Salmonella enterica serovars at single-cell level - Bin Wang; Bosoon Park; Bingqian Xu; Yongkuk Kwon (Journal of Nanobiotechnology, 2017)
Abstract Background The emerging nanotechnologies have greatly facilitated the development of label-free biosensors. The atomic force microscopy (AFM) has been used to study the molecular mechanism of the reactions for protein and aptamers. The surface plasmon resonance (SPR) have been used in fast detections of various pathogens such as bacteria. This study used both AFM and SPR to investigate the complex reactions between aptamers and outer membrane proteins (OMPs) on the surface of S. typhimurium. Results Two DNA aptamers were used for the label-free detections of S. typhimurium by AFM and SPR. The aptamers have specific binding affinities to the OMPs of S. typhimurium. At single-molecule level, the high resolution AFM topography and recognition images distinguished the OMPs on the bacteria surface, which is the first time the location of individual outer membrane protein have been determined on Salmonella surface. E. coli in the control experiments didn’t generate recognition signals, which proved the specificity of these two aptamers to S. typhimurium. The off-rate values for the interactions of these two aptamers to the OMPs were estimated as 5.2 × 10−3 and 7.4 × 10−3 s−1, respectively, by the AFM dynamic force microscopy (DFS). The force and extension values form DFS measurements were used to distinguish the two aptamers. The surface membrane model was proposed to explain the complex correlations among force and extension values. Next, these two aptamers were used in the bulk solution detections of S. typhimurium. The gold chips in SPR experiments were modified with carboxymethylated-dextran (CD), followed by aptamers immobilization, to reduce the non-specific binding signals. The limit of detection (LOD) was determined as 3 × 104 CFU mL−1. Conclusions The AFM single-molecule study revealed detailed information about the unbinding force and extension of the aptamer in complex biological reactions. The careful analysis of the experimental results provide better understanding of the molecular mechanism of OMPs reactions. The single-molecule measurements are helpful in evaluating the specificity of binding reagents, such as aptamers, in bulk solution detections. The protocols used in the SPR detections can be expanded into the label-free detections of other bacterial pathogens.